Association Between Bone Mineral Density and Body Composition in an Iranian Population: A Cross-Sectional Study - Alireza Askari; Maryam Abidi; Zahra Ghiasi; Mojtaba Farjam; Jalaledin Mirzay Razzaz; Reza Homayounfar (مجله علوم پزشکی صدرا, 2025)
Introduction: Osteoporosis has become increasingly prevalent worldwide. Given Iran’s unique climatic conditions and the paucity of comprehensive research in this field, this study aimed to investigate the relationship between body composition and bone mass density (BMD) in a random sample of the Iranian population. The findings aimed to inform more effective prevention and treatment strategies to reduce osteoporosis-related complications and associated healthcare costs.Methods: This cross-sectional study randomly selected 1500 participants, 570 men (38%) and 930 women (62%), aged >15 years from a health clinic in Tehran (Iran) during 2016-2017. Body composition and BMD were measured using dual-energy X-ray absorptiometry (DXA), with participants stratified into six Z-score categories based on their measurements.Results: The analysis revealed an inverse relationship between fat mass and BMD across all measured anatomical sites. Rank regression analysis identified three significant predictors of lumbar spine Z-scores, including sex (P=0.001), menopausal status (P=0.001), and trunk fat mass (P=0.001). Conclusion: These findings underscored the clinical importance of considering body composition parameters alongside BMD measurements in osteoporosis prevention and management. The results particularly highlighted the need for targeted interventions addressing modifiable risk factors, especially trunk adiposity, in at-risk populations.